Synthesis, Characterization and Antimicrobial Study of Co(II), Ni(II) and Cu(II) Complexes of 2-Phenyl-3-carboxy methyl quinazoline-(3H)-4-semicarbazone - Rai, B.K.; Sharma, K.K. (Asian Journal of Chemistry, 2010)
Complexes of semicarbazone of 2-phenyl-3-carboxy methyl quinazolin-(3H)-4-one with Co(II), Ni(II) and Cu(II) have been prepared and characterized by elemental analyses, spectroscopic data (IR and electronic), magnetic susceptibility, molar conductance measurements. From the analytical and spectral data, the stoichiometry of the complexes has been found to be 1:2 (metal:ligand). The ligand 2-phenyl-3-carboxy methyl quinazoline-(3H)-4-semicarbazone behave as neutral bidentate manner and coordination proposed through azomethine nitrogen and carbonyl oxygen of semicarbazone moiety. The remaining coordination positions are satisfied by anions Cl–, Br–, I– and NO3–. The above mentioned studies suggest the structure for the complexes are monomeric octahedral in geometry.